TOWARD A PRACTICALITY ETHIC FOR THE ADOPTION OF INNOVATIONS ON THE TRADITIONAL SIDE OF COMMUNICATIONS SYSTEMS - Leitch, Robert; Lidbetter, Kirk (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF